2018
DOI: 10.1080/14767058.2018.1424820
|View full text |Cite
|
Sign up to set email alerts
|

Can we stratify the risk for insulin need in women diagnosed early with gestational diabetes by fasting blood glucose?

Abstract: The need for insulin therapy in women with early diagnosis of GDM can be predicted by a logistic regression model, which can be converted to a clinically usable nomogram that could help to properly address follow-up strategies for GDM treatment in regions where health resources are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 11 publications
1
18
1
5
Order By: Relevance
“… 20 Factors such as maternal age, FH of diabetes, BMI at GDM diagnosis, and a prior GDM history have also been reported to increase the probability of insulin therapy. 11 , 19 We also observed that women with early-diagnosed GDM were more likely to require insulin intervention, which corroborates the findings of Alunni et al 21 Evidently, it would be imprecise to evaluate the risk of insulin requirement using isolated risk factors while ignoring individual differences. Our study quantified the above factors in a statistical prediction model, which we converted to a clinically usable nomogram that potentially illustrates the extent to which individual risk indicators contribute to the risk of insulin requirement.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“… 20 Factors such as maternal age, FH of diabetes, BMI at GDM diagnosis, and a prior GDM history have also been reported to increase the probability of insulin therapy. 11 , 19 We also observed that women with early-diagnosed GDM were more likely to require insulin intervention, which corroborates the findings of Alunni et al 21 Evidently, it would be imprecise to evaluate the risk of insulin requirement using isolated risk factors while ignoring individual differences. Our study quantified the above factors in a statistical prediction model, which we converted to a clinically usable nomogram that potentially illustrates the extent to which individual risk indicators contribute to the risk of insulin requirement.…”
Section: Discussionsupporting
confidence: 87%
“…A prediction model based on maternal age, pre-pregnancy BMI, FBG value, prior GDM, and FH of diabetes was developed from a retrospective cohort study in the Brazilian population. 11 Similarly, they also suggested maternal age, FBG value, prior GDM, and FH of diabetes as indicators of insulin requirement. However, the study focused exclusively on the need for insulin therapy in women with early GDM diagnosis, thereby ignoring GDM development in later trimesters.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…GDM patients were mainly manifested as postprandial 2-h hyperglycemia [59]. This may be due to the fact that the postprandial insulin secretion of pregnancies with normal glucose metabolism is earlier than that of GDM patients, and glucose is associated with fast recovery in GDM patients [60,61]. After black garlic fermentation with L. bulgaricus , insulin resistance was improved in GDM women.…”
Section: Discussionmentioning
confidence: 99%